Design of tunable power detector towards 5G applications. Issue 3 (7th October 2020) - Alaji, Issa; Aouimeur, Walid; Ghanem, Haitham; Okada, Etienne; Lépilliet, Sylvie; Gloria, Daniel; Ducournau, Guillaume; Gaquière, Christophe
Abstract: This paper presents the design and characterization of two tunable power detectors, based on PN diodes, integrated in SiGe 55‐nm BiCMOS technology from ST‐Microelectronics. The working frequency band of the circuits is (35‐50) GHz dedicated for 5G applications. The detector parameters are adjusted by controlling the biasing current, this characteristic makes them suitable to be utilized in different 5G applications. Two different diode sizes are used (L1N1, L2N5) in order to compare their performances. For three values of biasing current, the extracted voltage sensitivity values are between (700‐1400) V/W for L1N1 and (500‐1150) V/W for L2N5 showing the agreement with the simulation. Comparing to recent works, our designs exhibit very low power consumption (down to 60 nW) with relatively high sensitivity values. A targeted sensitivity value can be obtained with lower power consumption using larger diode size.